Strengthening The Religius and Honest Character of Students Through Tazkiyatun Nafs Guidance at Early Childhood Education - Muhammad Nofan Zulfahmi; Subaidi; Mudzakir Ali (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2026)
This study aims to examine and analyze the enhancement of students’ religious and honesty character through tazkiyatun nafs guidance in early childhood education settings. It employs a field research design, with data collected through observations, interviews, and documentation. The findings indicate that, first, religious character constitutes one of the key values cultivated in early childhood education, this character comes from Islamic teachings to Enhancing one’s relationship with God Almighty encompasses students’ thoughts, speech, and actions, all of which are consistently guided by religious values and principles.Through tazkiyatun nafs efforts, such as students being trained to pray, sholat, say greetings, read basmalah and hamdalah religious and honest characters are instilled in them, because prayer embedded divine values and at the same time the value of honesty; second, A fundamental objective of formal education is to cultivate honesty among students, because honesty is the basic capital in life.